2019
DOI: 10.2337/db18-1172
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Neuropilin-1 and -2 on Sensory Nerve Regeneration in Wounded Corneas: Role of Sema3C in Ameliorating Diabetic Neurotrophic Keratopathy

Abstract: The diabetic cornea exhibits pathological alterations, such as delayed epithelial wound healing and nerve regeneration. We investigated the role of semaphorin (SEMA) 3C in corneal wound healing and reinnervation in normal and diabetic B6 mice. Wounding induced the expression of SEMA3A, SEMA3C, and their receptor neuropilin-2 (NRP2), but not NRP1, in normal corneal epithelial cells; this upregulation was suppressed for SEMA3C and NRP2 in diabetic corneas. Injections of Sema3C- specific sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Experiments with two treatments and/or conditions were analyzed using a twotailed Student t test. Experiments with more than two groups were analyzed using one-way ANOVA, and if the experiments involved two independent variables (e.g., normal and diabetic, unwounded and wounded), a twoway ANOVA was used (8). Differences were considered statistically significant at P , 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments with two treatments and/or conditions were analyzed using a twotailed Student t test. Experiments with more than two groups were analyzed using one-way ANOVA, and if the experiments involved two independent variables (e.g., normal and diabetic, unwounded and wounded), a twoway ANOVA was used (8). Differences were considered statistically significant at P , 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes often present with decreased corneal wound healing, reduced corneal innervation, and a loss of corneal sensitivity (1)(2)(3)(4)(5)(6)(7)(8)(9). These complications of diabetes in the cornea are known as diabetic keratopathy (DK), which can lead to severe visual impairment (10).…”
mentioning
confidence: 99%
“…Nrp1, Nrp2 [108,109] Sema3A Not mentioned [110,111] Sema6A Not mentioned [112] Diabetic wound healing Sema4D PlexinB2 [113] Sema6A Not mentioned [114] Diabetic osteoporosis Sema3A Not mentioned [115][116][117][118]…”
Section: Sema3cmentioning
confidence: 99%
“…Wounding induced the expression of Sema3A, Sema3C, and their receptor Nrp2 in normal corneal epithelial cells, but the upregulation was inhibited in diabetic cornea. Exogenous Sema3C resulted in an increased rate of wound healing and nerve fiber regeneration, while Sema3C shRNAs and Nrp2-neutralizing antibodies had opposing effects to Sema3C in diabetic cornea [109]. Sema3C is also highly expressed in inflamed tissue in Charcot foot patients [108].…”
Section: Semaphorins In Diabetic Neuropathymentioning
confidence: 99%
“…Contrary to its inhibitory effects on embryonic neurons, we found that Sema3A is as effective as NGF in promoting neuronal elongation and branching in isolated adult PNS neurons and expedites nerve regeneration in vivo in mice that have undergone corneal subbasal nerve injury. Other groups have also found that supplementation with related Semaphorin proteins after corneal injury leads to improvement in epithelial and neuronal healing, including Sema3C and Sema 7A 13 , 14 .…”
Section: Introductionmentioning
confidence: 96%